AKSARA ARAB MELAYU DI KESULTANAN MELAYU - Marhamah Ulfa (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Antasari Banjarmasin, 2024)
Abstract: The background to this research is the development of the Malay Arabic script in Indonesia, which was initially influenced by the spread of Islam using the Arabic language. This research uses a literature review (research library) with qualitative methods based on sociolinguistic studies. The results of this research show that the Malay Sultanate paid attention to the Arabic-Malay script which is visible in the people of Riau, making Malay Arabic a local content subject in formal and non-formal education to preserve the Malay Arabic script. Keywords: Arabic-Malaya, Malay Sultanate Abstrak: Latar belakang penelitian ini adalah berkembangnya aksara arab melayu di Indonesia yang awalnya dipengaruhi oleh persebaran agama islam dengan bahasa arab. Penelitian ini menggunakan kajian pustaka (library riset) dengan metode kualitatif berdasarkan kajian sosiolingustik. Hasil penelitian ini menunjukkan bahwa kesultanan melayu memberikan perhatian terhadap aksara arab-melayu yang terlihat pada masyarakat yang berada di Riau menjadikan bahasa Arab Melayu sebagi mata pelajaran muatan lokal pada pendidikan formal dan non-formal untuk melestarikan aksara Arab Melayu Kata Kunci: Arab-Melayu, Kesultanan Melayu